Dampak Globalisasi, Nilai Tambah Industri dan Ekspor Pertanian terhadap Keberlanjutan Lingkungan di Indonesia dan Jepang : Analisis Model ARDL - Putri, Mega Amelia; Tan, Firwan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Indonesia and Japan have different potentials and uniqueness, but the value of agricultural exports, industrial added value and globalization will still cause environmental degradation. This study aims to find out how globalization, agricultural exports and industrial value added have an impact on environmental sustainability. In particular, were proposed using secondary data, from 1990 to 2020. The model was estimated using the ARDL procedure. The result, in the short term social globalization in Japan has a positive and significant impact on increasing CO2 emissions from the use of on-farm energy (EMS). Likewise, the added value of the agricultural industry can exacerbate the increase in EMS both in the short and long term. Meanwhile, the added value of agriculture in the short term can reduce EMS, a significance of 5%. However, in the long run the added value of the industry can reduce EMS, a significance of 5%. In contrast, with Indonesia in the short term agricultural exports have a positive and significant impact on EMS. While added value in the short term and in the long term can reduce EMS, a significance of 5%. However, SG in the long run will exacerbate EMS. Therefore, we propose recommendation to improve this condition, including a clear roadmap, increased partnerships, and regional and international support in order to produce policies that are able to preserve the environment, especially in the agricultural sector.